Experiences of Productive-Age Diabetes Mellitus Patients in Maintaining Kidney Function through Healthy Lifestyle Changes - Sulastri, Weni; Yani, Sutri; Hibatullah, Fatih; Dewa Darma, Dimas (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Diabetes Mellitus (DM) in productive-age patients is a public health challenge. One of the serious complications of DM is impaired kidney function. Healthy lifestyle changes have the potential to help maintain kidney function, but understanding of patient experiences in maintaining kidney function through a healthy lifestyle is still limited. This study aims to explore the experiences of productive-age DM patients in their efforts to maintain kidney function through healthy lifestyle changes. Methods: This study used a qualitative research method with a phenomenological approach. A purposive sample of productive-age DM patients aged 20–45 who had undergone DM therapy for at least 2 years was selected. Data were collected through in-depth interviews, recorded, transcribed, and then analyzed using thematic analysis. The results of this study examined patient experiences in terms of knowledge about kidney risks, motivation to make lifestyle changes, challenges and barriers, adaptation strategies, the role of family/environmental support, and perceptions about efforts to maintain kidney function. Conclusion: A thorough understanding of patient experiences can assist nurses and healthcare teams in designing educational interventions and healthy lifestyle support tailored to the needs of productive-age DM patients.